The Role of Teachers in Preventing Bullying in Elementary Schools - Djapri, Yani; Asrori, Muhammad; Halidjah, Siti; Ghasya, Dyoty Auliya Vilda (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
Bullying at school base is problem serious that requires handling systematic. The teacher plays role central in prevention bullying, no only as educator but also a facilitator climate positive class. Review​ systematic This analyzed 16 articles selected from the Scopus and PubMed databases using PRISMA method for explore strategy effective prevention. Research results show that the prevention program based school like KiVa, SUBS, and PRIMA are proven effective when supported by fidelity and quality implementation high. Intervention based wisdom local, such as Tri Hita Karana e-worksheets and animations Balinese fable "Tat Twam" Asi ", also shows effectiveness in increase literacy and prevention bullying. The review also revealed complexity factor psychological, including paradox connection between empathy and behavior child bullying​ man as well as impact term long bullying that can ongoing until adult approach​ comprehensive and sustainable that involves all over community school very required